CD5+ B Cells Ratio In Lepromatous Leprosy - Ilhan, F.; Cicek, D.; Godekmerdan, A.; Tahran, G.; Bulut, V (Premchand Shantidevi Research Foundation, 2007)
Objective Leprosy is a unique infectious disease, which is chronic and related to cellular immunity. It was known that who have a defect on cellular immunity, they are susceptible to M. leprae infection. CD19+CD5+B cells are currently defined as B1 cells and they produce polyreactive antibodies. The aim of this study was to investigate the presence and the possible effect of natural antibody producing CD19+ CD5+ B cells in leprosy disease patients. Materials and Methods We investigated B lymphocyte subset and total B and B1 cells by flow cytometry in 40 patients with lepromatous leprosy and 40 healthy controls. Results Compared to the healthy controls, both CD19+ CD5- conventional B cells and CD19+ CD5+ B1 cells subsets were found to be higher in leprosy patients group. Conclusion The observed significant increases in CD19+ CD5- and CD19+ CD5+ B1 cells subsets in patients with lepromatous leprosy suggests that B1 lymphocytes known predisposed to autoimmunity may have a role on disorganized protective immune response in Lepromatous leprosy.
Keywords: lepromatous leprosy; CD19+ CD5+ B cells; Mycobacterium leprae